Seven cases of dermatitis caused by benzalkonium chloride disinfectant - Qian ZHANG; Liyan YUAN; Ruzeng XUE; Wei WEN; Shiqi LING; Suyun JI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Objective To analyze the clinical manifestations and histopathological features of 7 cases of dermatitis caused by benzalkonium chloride disinfectant, so as to enhance the understanding of this disease. Methods We retrospectively analyzed the clinical manifestations and pathological features of benzalkonium disinfectant-induced contact dermatitis in 7 cases who visited our clinic from August to November 2022. Results The clinical manifestations were repeated annular erythema and desquamation at the rubbing sites of the skin. The histopathological features of 4 cases were sponge formation, acanthosis and perivascular inflammation in the superficial dermis. Accumulation of neutrophils in the epidermis and the dermis was observed in 2 cases. Patients were treated with the systemic glucocorticoids and cyclosporine, and advised to avoid contact with benzalkonium chloride disinfectant. Conclusions Contact dermatitis caused by benzalkonium chloride disinfectant has specific manifestations and good response to the treatments. The skin patch test would be helpful to confirm the diagnosis.